ESG Disclosure, Intellectual Capital, and Firm Financial Performance: The Role of Board Gender Diversity as a Moderator - Muhammad Pondrinal; Elvira Luthan (Universitas Muhammadiyah Malang, 2026)
This study examines whether ESG disclosure and intellectual capital affect Indonesian banks’ financial performance and whether board gender diversity (BGD) moderates these effects. Panel data from 14 IDX-listed banks during 2019–2023 (n = 70 firm-year observations) were analyzed using a Random Effect Model and Moderated Regression Analysis in EViews 12. ROA represents financial performance; ESG is a GRI-based disclosure index; intellectual capital is measured by VAIC; and BGD is the proportion of female directors. Results show ESG disclosure improves ROA (β = 0.010735; t = 2.199; p = 0.031), whereas intellectual capital is negative and not significant (β = −0.000196; t = −0.112; p = 0.911) and BGD has no significant direct effect (β = −0.015360; t = −1.292; p = 0.201). The baseline model explains modest variation in ROA (R² = 0.093; adjusted R² = 0.052). Interaction tests indicate that BGD strengthens the ESG–ROA link at the 10% level (βESG×BGD = 0.080093; p = 0.055) and significantly strengthens the intellectual capital–ROA link (βIC×BGD = 0.022174; t = 2.762; p = 0.007), suggesting gender-diverse boards help convert sustainability transparency and knowledge-based resources into profitability. The study contributes to Resource-Based Theory and Stakeholder Theory by showing that governance diversity is a boundary condition for realizing performance payoffs from ESG disclosure and intellectual resources in an emerging-market banking context. Practically, banks should enhance ESG reporting quality, improve intellectual-capital efficiency, and increase female representation in boards and key committees to strengthen oversight and strategic use of intangible assets. Overall, the findings highlight inclusive governance as a strategic lever to amplify the financial benefits of ESG disclosure and intellectual capital in Indonesian banking.